2015
DOI: 10.1016/j.bbmt.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Post-Thaw Viable CD45 + Cells and Clonogenic Efficiency are Associated with Better Engraftment and Outcomes after Single Cord Blood Transplantation in Adult Patients with Malignant Diseases

Abstract: The quantity of cells is widely accepted as the main factor influencing the outcome after umbilical cord blood transplantation (UCBT) however, the quality of the cord blood units (CBUs) has been less studied. In order to determine the impact of qualitative variables in UCBT outcomes, we conducted a multicenter retrospective study in adult patients with hematological malignancies who underwent single UCBT after a common myeloablative conditioning regimen. One hundred and ten patients from 3 institutions [median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Seeding was based on the prefreezing CD341 cell counts as determined using the singleplatform ISHAGE protocol and results are reported as the number of colony-forming units (CFUs)/1000 CD341 cells. 14 The final remaining DMSO concentration ranged from 0.023% to 0.23%, which have negligible effects for in vitro assays. 15 The cells were cultured for 14 days in sixwell plates (Falcon, Becton Dickinson) at 378C, under 5% CO 2 .…”
Section: Detection and Quantification Of Progenitorsmentioning
confidence: 99%
“…Seeding was based on the prefreezing CD341 cell counts as determined using the singleplatform ISHAGE protocol and results are reported as the number of colony-forming units (CFUs)/1000 CD341 cells. 14 The final remaining DMSO concentration ranged from 0.023% to 0.23%, which have negligible effects for in vitro assays. 15 The cells were cultured for 14 days in sixwell plates (Falcon, Becton Dickinson) at 378C, under 5% CO 2 .…”
Section: Detection and Quantification Of Progenitorsmentioning
confidence: 99%
“…One of these criteria is the determination of the regenerative potential—namely, potency—of the cryopreserved unit. Potency is a measure of the biologic activity of cord blood stem cells, which enables the generation of hematopoietic progenitors The assessment of potency in CBUs to predict their capacity for engraftment is a task that is not standardized and involves a long delay for CBBs and transplant centers.…”
mentioning
confidence: 99%
“…The CFU method consists of culturing cells in vitro in a methylcellulose medium containing a mix of growth factors such as stem cell factor, interleukin (IL)‐3, IL‐6, granulocyte colony‐stimulating factor, granulocyte‐macrophage colony‐stimulating factor and erythropoietin. High‐quality CFU dose after thawing is generally considered to be a very good indicator of the CBU capacity to achieve neutrophil and platelet engraftment in clinically acceptable time However, this assay has some drawbacks. Most importantly, the CFU method needs 7 to 14 days of incubation before the colonies can be counted.…”
mentioning
confidence: 99%
“…Therefore, measuring clonogenic efficiency is more appropriate to describe cell viability and proliferation capacity, as post thaw clonogenic efficiency is associated with better engraftment and outcome in cell therapy. 3 In addition, Kusuma et al 1 study measured viability by water-soluble tetrazolium-1 (WST-1) proliferation assay, which might give a higher viability result, as WST-1 measured metabolic activity, and cryopreserved cells were reported to have increased metabolic activity. 2 Moreover, WST-1 proliferation assay in Kusuma et al 1 study showed absorbance that was not interpolated to viable cell numbers, thus could not be compared to other cryopreservation studies that measured viable cell numbers using trypan blue exclusion.…”
mentioning
confidence: 99%
“…7 When a high number of post thaw senescent cells are recultured, they lose their proliferation capacity and force non-senescent cells to proliferate more to become confluent, thus increases their cumulative population doublings to reach their Hayflick limit, and so non-senescent cells will become senescent, increasing the senescent cell population. A study showed that post thaw clonogenic efficiency of umbilical cord blood hematopoietic progenitor cells after cryopreservation in DMSO containing cryo-medium was 22%, 3 which means that only 22% of post thaw cells can proliferate. Reduced post thaw clonogenic efficiency might play a role in increased proportion of senescent cells, and thus their functional performance.…”
mentioning
confidence: 99%